ON STRUCTURED AND DIFFUSE SEISMICITY, STIFFNESS OF EARTHQUAKE FOCI, AND NONLINEARITY OF MAGNITUDE RECURRENCE GRAPHS - Evgeny G. Bugaev (Геодинамика и тектонофизика)
Geological, geophysical and seismogeological studies are now conducted in a more detail and thus provide for determining seismic sources with higher accuracy, from the first meters to first dozens of meters [Waldhauser, Schaff, 2008]. It is now possible to consider uncertainty ellipses of earthquake hypocenters, that are recorded in the updated Earthquake Catalogue, as surfaces of earthquake focus generators. In our article, it is accepted that a maximum horizontal size of an uncertainty ellipse corresponds to an area of a focus generator, and seismic events are thus classified into two groups, earthquakes with nonstiff and stiff foci. Criteria of such a classification are two limits of elastic strain and brittle strain in case of uniaxial (3⋅10–5) or omnidirectional (10–6) compression. The criteria are established from results of analyses of parameters of seismic dislocations and earthquake foci with regard to studies of surface parameters and deformation parameters of fault zones. It is recommendable that the uniaxial compression criterion shall be applied to zones of interaction between tectonic plates, and the unilateral compression criterion shall be applied to low active (interplate) areas. Sample cases demonstrate the use of data sets on nonstiff and stiff foci for separate evaluation of magnitude reoccurrence curves, analyses of structured and dissipated seismicity, review of the physical nature of nonlinearity of recurrence curves and conditions of preparation of strong earthquakes. Changes of parameters of the recurrence curves with changes of data collection square areas are considered. Reviewed are changes of parameters of the recurrence curves during preparation for the Japan major earthquake of 11 March 2011 prior to and after the major shock. It is emphasized that it is important to conduct even more detailed geological and geophysical studies and to improve precision and sensitivity of local seismological monitoring networks in zones of nuclear stations and other hazardous facilities. It is noted that a list of parameters recorded in earthquake catalogues needs to be extended. Based on the above, it will be possible to ensure proper monitoring of stability of the seismic process during construction, operations and decommissioning of nuclear stations.